2010
DOI: 10.1016/j.taap.2009.05.025
|View full text |Cite
|
Sign up to set email alerts
|

ROS signaling, oxidative stress and Nrf2 in pancreatic beta-cell function

Abstract: This review focuses on the emerging evidence that reactive oxygen species (ROS) derived from glucose metabolism, such as H 2 O 2 , act as metabolic signaling molecules for glucose-stimulated insulin secretion (GSIS) in pancreatic beta-cells. Particular emphasis is placed on the potential inhibitory role of endogenous antioxidants, which rise in response to oxidative stress, in glucosetriggered ROS and GSIS. We propose that cellular adaptive response to oxidative stress challenge, such as nuclear factor E2-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
206
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(213 citation statements)
references
References 110 publications
(147 reference statements)
4
206
0
3
Order By: Relevance
“…Atg7 Δpan pancreata contained high amounts of Ucp2 mRNA (Fig. S3B), encoding a mitochondrial protein located on the inner mitochondrial membrane, involved in adaptive response to mitochondria-derived ROS and oxidative damage (31).…”
Section: Loss Of Atg7 Results In Er Stress and Mitochondrial Dysfunctmentioning
confidence: 99%
“…Atg7 Δpan pancreata contained high amounts of Ucp2 mRNA (Fig. S3B), encoding a mitochondrial protein located on the inner mitochondrial membrane, involved in adaptive response to mitochondria-derived ROS and oxidative damage (31).…”
Section: Loss Of Atg7 Results In Er Stress and Mitochondrial Dysfunctmentioning
confidence: 99%
“…1); however, there were some unique differences. The commonly used MPC inhibitor ␣-CHC has been shown to inhibit insulin secretion in some studies (29 -31), stimulate in others (33,34), and do nothing in other studies (32). For most of these studies in ␤-cells, they have used a 1 mM ␣-CHC concentration, which is also known to inhibit PC (44).…”
Section: Pharmacological Inhibition Of the Mpc Reduces Gsis In 832/13mentioning
confidence: 99%
“…This inhibitor has facilitated experiments to determine the contribution of mitochondrial pyruvate transport to GSIS, yielding inconsistent results. Studies in rat islets (29), HIT cells (30), and MIN6 cells (31) showed that inhibition of pyruvate transport blocked GSIS, whereas a study with 832/13 cells showed no effect (32), and two other studies showed in mouse (33) and rat islets (34) that pyruvate transport inhibition leads to a stimulation of insulin secretion. A more potent mitochondrial pyruvate carrier inhibitor, ␣-cyano-␤-(1-phenylindol-3-yl)-acrylate (UK5099), which is now commercially available, has not yet been tested in ␤-cells (28).…”
mentioning
confidence: 99%
“…In this special context, the disruption of the uncoupling mitochondrial protein-2 (UC-2) into the inner membrane has been associated with a phenotype of massive and chronic free radical release [67].…”
Section: Molecular Pathways Of Diabetes Mellitus Pathogenesismentioning
confidence: 99%
“…In the same context, beta cells can adapt against free radical damage by expressing the nuclear-factor E2-related factor (Nrf-2) which triggers the expression of many different antioxidant genes, helping to rescue beta cells from the genotoxic free radical insults [67]. The Nrf-2 induction leads to expression of antioxidant genes and attenuation of the NFkB inflammatory pathway protecting endothelium, the nephron, and other structures against hyperglicemic-load induced toxicity [83][84][85][86].…”
Section: Molecular Pathways Of Diabetes Mellitus Pathogenesismentioning
confidence: 99%